Suction assisted surgical extraction of subcutaneous lipoma - Bhoir, Lata N.; Sharma, Neha D.; Pishe, Vishal M. (International Journal of Research in Medical Sciences, 2024)
Background: Lipomas are the most common benign mesenchymal tumours in the body. Patients seek their removal due to disfigurement, discomfort or cancerphobia. Historically, open surgical removal was the mainstay of their treatment but striving for less scarring, liposuction is the only new FDA approved alternative. Methods: 56 patients with subcutaneous lipoma of size 3 cm - 10 cm and fulfilling eligibility criteria were selected for this hospital based prospective cohort study after informed consent and Institutional Ethical Committee approval from June 2016 to July 2018. 3 mm irrigation cannula, 5 mm suction cannula, Suction holding tool and Luer lock syringe were used. Lipoma infiltrated with modified Klein solution. Lipoma suctioned out & through the same port, capsule in the cavity was pulled out employing long forceps. Results observed with regards to operative time, post-operative scars, post operative pain and recurrence. Result: A total of 56 patients were enrolled, operated, and observed. Mean duration of lipoma removal surgery was 47.32 minutes. 67.85% patients had pain score 1 after 2 hours of surgery. 100% of patients had healthy scars. 80.4% patients had 0 Vancouver Scarscore after 6 month follow up and only 1 patient had recurrence in 5 months. Conclusions: Our study showed good results in view of postoperative pain and quality of scar. Use of 5 mm cannula gave visually negligible scar with less than 2% recurrence rate. Even though the mean duration of surgery was 47 mins which is more compared to open excision, the good cosmetic result with minimal to no scar prevails over it.